Spectral-domain optical coherence tomography combined with electroretinography in the assessment of conbercept for neovascular age-related macular degeneration: a preliminary study - Wang, Xing; Wang, Peng (Frontiers in Neuroscience, 2023)
Objective: To observe the effect of three consecutive intravitreal injections of conbercept in the treatment of neovascular age-related macular degeneration (nAMD), to investigate the correlation between retinal anatomy and retinal function by spectral-domain optical coherence tomography (SD-OCT) and electroretinography (ERG), to evaluate the short-term clinical efficacy of conbercept in the treatment of nAMD, and to explore the value of ERG as a predictor of treatment efficacy. Method: A retrospective investigation was conducted on 36 patients (36 eyes) treated with intravitreal injections of conbercept at 0.5 mg a month for three consecutive courses. Data collected included the best corrected visual acuity (BCVA), central retinal thickness (CRT), retinal pigment epithelium (RPE) elevation volume in 1 mm-diameter (1RV), 3 mm-diameter (3RV), and 6 mm-diameter circles around the fovea (6RV) , amplitude density and latency of the P1 wave in the multifocal electroretinography (mf-ERG) R1 ring and amplitude and latency in full-field electroretinography (ff-ERG) at baseline and monthly. The paired t test was used to compare the difference between pre- and posttreatment. Pearson correlation analysis was used to analyse the correlation between macular retinal structure and function. The difference was significant when P < 0.05. Results: At 12 weeks, the BCVA, CRT, 1RV, 3RV, 6RV, the P1 wave amplitude density of the mf-ERG R1 ring and the ff-ERG amplitude parameters were all significantly improved (P<0.001). The BCVA in logMAR was positively correlated with CRT; 1RV, 3RV, and 6RV were negatively correlated with the amplitude density and latency of the mf-ERG R1 ring P1 wave . There were no severe ocular or systemic complications during the follow-up period. Conclusion: Conbercept is useful for the short-term treatment of nAMD. It can safely improve the visual acuity of affected eyes and restore the structure and function of the retina. ERG could serve as an objective indicator of function for evaluating the efficacy of and determining the need for retreatment during nAMD treatment.